Development and evaluation of a triplex real-time PCR assay for enhanced plague diagnostics in Madagascar. - Beza Ramasindrazana; Zoé A Rahalison; Philippe Gauthier; Guillain Mikaty; Zaina I Bodoarison; Lanto A Maminirina; Soloandry Rahajandraibe; Mamy G Randriamanantsoa; Gilbert Kayoko; Jean-Claude Manuguerra; Anne-Sophie Le Guern; Andriamiliharison J Rasamindrakotroka; et al. (PLoS Neglected Tropical Diseases)
Background The plague, caused by Yersinia pestis, remains a critical public health issue, particularly in endemic regions like Madagascar. Rapid and accurate detection of this pathogen is essential for effective outbreak management and timely intervention. Following the urban plague outbreak of 2017, a new molecular diagnostic algorithm was developed and introduced into routine use. However, certain cases required combining real-time and conventional polymerase chain reaction (PCR) methods. While effective, this approach often delayed obtaining conclusive results, an issue that can hinder swift outbreak responses. The aim of this study is to design and optimize a three-target real-time PCR assay (qPCR) for the detection of Y. pestis in clinical samples. Methods The assay targeted three genes: caf1, pla, and yopM, located on the plasmids pMT1, pPCP1, and pCD1, respectively. Conducted at the Institut Pasteur de Madagascar (IPM), the study evaluated the assay using both pure bacterial cultures and clinical samples, including 50 bubonic aspirates and 50 respiratory specimens. Results Using bacteriology technique as the reference standard, the triplex qPCR demonstrated a sensitivity of 100% (89-100%) and a specificity of 82%. The positive predictive value (PPV) was 73% and the negative predictive value (NPV) was 100% (91-100%). The coefficient of agreement kappa was 0.74, with a p-value of <0.0001. Notably, the new assay resolved 100% of previously inconclusive cases from the duplex qPCR test targeting only pla and caf1. Discussion While a new plague diagnostic algorithm has been set up after the outbreak in 2017, the present study suggests a real-time PCR assay based on three genes to improve the speed and accuracy of plague diagnostic. Furthermore, this new technique is a valuable tool for managing plague outbreaks and supporting field diagnostics not only in Madagascar but also in countries with plague. Conclusions The developed triplex assay to molecularly diagnose Y. pestis in human samples improves the standard already in place and allows to resolve ambiguities previously associated with inconclusive results from duplex qPCR tests, thereby reinforcing the reliability and accuracy of this new technique. Implementing this new method into routine will enable a faster, more effective response to plague outbreaks by reducing the time needed to confirm plague cases and limiting the spread of the diseases. This new technique is also flexible and can be undertaken close to human cases with adequate biosecurity and biosafety measures.